2022
DOI: 10.1186/s12882-022-02892-7
|View full text |Cite
|
Sign up to set email alerts
|

Can residual kidney function affect quality of life and cognitive function in hemodialysis patients?

Abstract: Background Residual kidney function (RKF) may provide many benefits to patients on permanent renal replacement therapy that are reflected in better control of biochemical parameters. In hemodialysis patients, quality of life (QOL) and cognitive function are often impaired. This study aimed to assess the predictors of RKF and its impact on QOL and cognitive function in chronic hemodialysis patients. Patients and methods The study involved seventy-ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Observational studies examining QOL in incremental HD are limited 6,18 and a systematic review and meta-analyses comparing incremental to standard-dose dialysis has not addressed QOL as an outcome. 12 However, better preservation of RKF has been shown to improve health-related-quality-of-life in the HD population, 27 and an incremental approach may support greater RKF. Broader consumer involvement in trial design to enrich key outcomes of interest will further improve HD treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies examining QOL in incremental HD are limited 6,18 and a systematic review and meta-analyses comparing incremental to standard-dose dialysis has not addressed QOL as an outcome. 12 However, better preservation of RKF has been shown to improve health-related-quality-of-life in the HD population, 27 and an incremental approach may support greater RKF. Broader consumer involvement in trial design to enrich key outcomes of interest will further improve HD treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The patients may get benefi ts from residual renal function, such as control of biochemical parameters, 78 patients in Dialysis unit of Mansoura University Hospitals underwent regular hemodialysis for more than 6 months; the patients with preserved residual renal function had better quality of life and cognitive function [5]. There is a decline in residual renal function in the fi rst year of hemodialysis with the mean urine volume of 1 cc per month, in 2021, in literature review of medical and nursing journals focusing on residual renal function within the fi rst year post hemodialysis initiation, the median baseline and one year after, the urine volume was 900 cc and 650 cc respectively, the furosemide played a major role in lowering the rate of decline, the high urine volume was associated with lower mortality [6].…”
Section: Discussionmentioning
confidence: 99%
“…Reducing the frequency of dialysis can potentially reduce the repeated insults to the brain and decrease the rate of cognitive decline. Greater preservation of residual kidney function, as reported in observational studies of incremental dialysis, can potentially preserve the self-reported health quality of life and cognitive assessment scores of older patients treated with haemodialysis [22]. Thus, starting with incremental dialysis may have significant benefits with regard to preventing the rapid cognitive decline reported in studies of elderly patients treated with conventional thriceweekly dialysis schedules.…”
Section: Frequency Of Dialysis: Should Incremental Dialysis Be the Fi...mentioning
confidence: 99%